Randomized, double blind, placebo-controlled, safety and efficacy study of dutogliptin in combination with filgrastim in early recovery post-MI: rationale, design and first interim analysis. (25th November 2020) - Von Lewinski, D; Merkely, B; Buysschaert, I; Schatz, R.A; Nagy, G.G; Kiss, R.G; Henauer, S; Wallner, M
Abstract: Background: Regenerative therapies offer new approaches to improve cardiac function after acute ST-elevation myocardial infarction (STEMI). Mobilization of stem cells and homing within the infarcted area have been identified as the key mechanisms for successful treatment. Application of granulocyte-colony stimulating factor (G-CSF) is the least invasive way to mobilize stem cells while DDP4-inhibitor facilitates homing via stromal cell-derived factor 1 alpha (SDF-1α). Dutogliptin, a novel DPP4 inhibitor, combined with stem cell mobilization using G-CSF significantly improved survival and reduced infarct size in a murine model. Purpose: We initiated a phase II, multicenter, randomized, placebo-controlled efficacy and safety study (N=140) analyzing the effect of combined application of G-CSF and dutogliptin, a small molecule DPP-IV-inhibitor for subcutaneous use after acute myocardial infarction. Methods: The primary objective of the study is to evaluate the safety and tolerability of dutogliptin (14 days) in combination with filgrastim (5 days) in patients with STEMI (EF <45%) following percutaneous coronary intervention (PCI). Preliminary efficacy will be analyzed using cardiac magnetic resonance imaging (cMRI) to detect >3.8% improvement in left ventricular ejection fraction (LV-EF). 140 subjects will be randomized to filgrastim plus dutogliptin or matching placebos. Results: Baseline characteristics of the first 26 patients randomized (24 treated) in this trial reveal a majority of male patients (70.8%) and a medium age of 58.4 years (37 to 84). During the 2-week active treatment period, 35 adverse events occurred in 13 patients, with 4 rated as serious (hospitalization due to pneumonia N=3, hospitalization due to acute myocardial infarction N=1), and 1 adverse event was rated as severe (fatal pneumonia), 9 moderate, and 25 as mild. 6 adverse events were considered possibly related to the study medication, including cases of increased hepatic enzymes (N=3), nausea (N=1), subcutaneous node/suffusion (N=1) and syncope (N=1). Conclusions: Our data demonstrate that the combined application of dutogliptin and G-CSF appears to be safe on the short term and feasible after acute myocardial infarction and may represent a new therapeutic option in future. Funding Acknowledgement: Type of funding source: Other. Main funding source(s): This research is funded by the sponsor RECARDIO, Inc., 1 Market Street San Francisco, CA 94150, USA. RECARDIO Inc. is funding the complete study. The Scientific Board of RECARDIO designed the study. Data Collection is at the participating sites. Interpretation of the data by the Scientific Board and Manuscript written by the authors and approved by the Sponsor